The associations between physical-test performance and match performance in women’s rugby sevens players - Sella, Francesco; Hopkins, William; Beaven, Christopher; McMaster, Daniel; Gill, Nicholas; Hébert-Losier, Kim (Biology of Sport, 2023)
Evaluating the relationships between physical-test and match performance in team sports could be useful for training prescription and athlete evaluation. Here we investigated these relationships in women’s Rugby Sevens. Thirty provincial-representative players performed Bronco-fitness, countermovement-jump, acceleration, speed, and strength tests within two weeks before a two-day tournament. Match-running and match-action performance measures were provided by GPS units and video analysis. Generalised and general linear mixed models were employed to estimate the effect of a two standard-deviation difference in physical test measures on match measures. Effect magnitudes were assessed via standardisation (using the between player SD) and, for effects on tries scored, also via match winning (based on simulating matches). Evidence for substantial and trivial true magnitudes was provided by one-sided interval-hypothesis tests and Bayesian analysis. There was good evidence of positive effects of many physical-test measures on match high-intensity running, with large effects for jump height and acceleration. There was some evidence of small-moderate positive effects of speed and Bronco, and of small-moderate negative effects of maximal strength and jump height, on match total running and high intensity changes in speed. The evidence was generally inadequate for associations between physical-test measures and match actions, but there was good evidence of small-large positive effects of back squat and jump height on tries scored. Enhancing players’ jump height and back-squat performance might therefore increase the likelihood of match success in women’s Rugby Sevens.